POLA KOMUNIKASI TRAINER DALAM TRAINING ESQ PEKANBARU - Irvan Ayubi; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
ESQ training is a form of instructional communication through the process of delivering messages (training material) by a communicator (trainer) to the recipient of the message (training participants) with programmatic planning and follow-up so that learning and training objectives (training) are achieved well. In training, communication patterns generally occur with the communicator and the communicant. This pattern of communication has an important role in the success of a communication which then impacts the training output later.            The method used in this study is a qualitative method, with the presentation of a descriptive analysis. The technique of taking informants in this study is to use a purposive technique, which is used as a member of the informant submitted to the consideration of collecting data based on its consideration in accordance with the aims and objectives. This study uses data collection techniques through observation, interviews, and literature studies to achieve the validity of the data in this study.            The results showed that the communication patterns applied by trainers in the ESQ (Emotional Spiritual Quotient) training were two-way communication patterns. Two-way communication is communication that is communicant and communicators always take turns providing information in delivering a message. In short, communication takes place between the giver of information and the recipient of information. When the information provider conveys information then the recipient of the information will respond to a message delivered. In communicating the message delivered by the communicator, based on the assumptions of Aristotle's Theory states that what the speaker is doing in preparation for delivering their message and in limiting the message. This assumption refers to the way of persuasion, which is contained in three evidences, namely ethos, pathos and logos.Keywords : Communication Pattern, Trainer, Training, ESQ, Rhetoric